Family-Owned Newspapers: Filling Niches in Local U.S. Communities - Powers, Angela M.; Sohn, Ardyth B.; Briggs-Bunting, Jane (My University, 2016)
Since small town newspapers are facing increased competition and technological changes that are threatening their survival, the purpose of this paper was to analyze the strategy-making activities of these organizations from an ecological perspective. Findings indicate that family-owned newspapers were finding stability in retaining their core print businesses while migrating content to the web. Too many variations from the norm appeared to weaken financial footholds and were often eventually abandoned. Such behaviors indicate a rationale for upholding a “tried-and-true” approach in newspapers. While profits may fluctuate, the uncertainty that occurred with variation seemed to play a role in increasing the threat of failure for these small, family-owned newspapers.
Citation: Powers, A., Sohn, A. B., Briggs-Bunting, J. (2016) Family-Owned Newspapers: Filling Niches in Local U.S. Communities. Journal of Media Business Studies. 2(11)
Keywords: Media Ecology; Newspapers; News Media; Niches; Family Newspapers; Organizational Ecology